Introduction - Tsyrempilov, Nikolay (Etudes Mongoles et Siberiennes, Centrasiatiques et Tibetaines, 2016)
Present-day scholarship on the Buryats, or Buryat-Mongols, consciously or otherwise considers the people in question and the areas they inhabit as a marginal part or periphery of the Mongolian or Russian worlds ; the logic of this marginality is determined by the history of this ethno-cultural group formation at the civilizational juncture between Asia and Europe, and furthermore acquires its historical and cultural identity from this marginality. Indeed, most of the few Western Buryatologists approach their area specialization from one of two dominant perspectives. The majority of them initially had, and still have, an established basic interest in Russian studies or, to be precise, studies in Russian Siberia. In this perspective the Buryats are viewed as the largest indigenous people of Siberia, culturally and historically one of the most curious minorities of Asiatic Russia.
Keywords: Buriats; Mongolian studies; Russian studies